2015
DOI: 10.1111/fcp.12163
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical determination of the extracellular matrix modulation in a rat model of choline‐deprived myocardium: the effects of carnitine

Abstract: Choline has been identified as an essential nutrient with crucial role in many vital biological functions. Recent studies have demonstrated that heart dysfunction can develop in the setting of choline deprivation even in the absence of underlying heart disease. Matrix metalloproteinases (MMPs) are responsible for extracellular matrix degradation, and the dysregulation of MMP-2 and MMP-9 has been involved in the pathogenesis of various cardiovascular disorders. The aim of the study was to investigate the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 88 publications
(123 reference statements)
1
13
0
Order By: Relevance
“…Moreover, choline deficiency induced dysregulation of MMPs/TIMPs in rat myocardial tissue, through significant decrease in MMP-2/TIMP-2 ratio which confirm the increases in extracellular matrix turnover state in rat myocardium induced by a dietary choline deficiency; the studied ratio of MMP-2/TIMP-2 reflecting the ECM dynamics that are indispensable during restructuring of tissue architecture confirmed that dietary deprivation of choline triggers collagen accumulation and deposition leading to cardiac interstitial fibrosis (Strilakou et al, 2016). MMPs are interfering with cell proliferation, differentiation, inflammation and triggering of angiogenesis via increase of VEGF expression in heart (Sang, 1998;Okazaki et al, 2014).…”
Section: Choline Deficiency Induces Cardiovascular Injurysupporting
confidence: 55%
See 2 more Smart Citations
“…Moreover, choline deficiency induced dysregulation of MMPs/TIMPs in rat myocardial tissue, through significant decrease in MMP-2/TIMP-2 ratio which confirm the increases in extracellular matrix turnover state in rat myocardium induced by a dietary choline deficiency; the studied ratio of MMP-2/TIMP-2 reflecting the ECM dynamics that are indispensable during restructuring of tissue architecture confirmed that dietary deprivation of choline triggers collagen accumulation and deposition leading to cardiac interstitial fibrosis (Strilakou et al, 2016). MMPs are interfering with cell proliferation, differentiation, inflammation and triggering of angiogenesis via increase of VEGF expression in heart (Sang, 1998;Okazaki et al, 2014).…”
Section: Choline Deficiency Induces Cardiovascular Injurysupporting
confidence: 55%
“…We have previously reported the early deleterious effect of Ch-deprivation on the adult healthy rat myocardium (Strilakou et al, 2013) (Strilakou et al, 2016). We herein provide novel findings that Chdeprivation aggravates the myocardial architecture and potential performance in STZ-induced diabetic adult rats.…”
Section: Effect Of Dietary Choline-deprivation On Diabetic Cardiomyopathy In Ratmentioning
confidence: 50%
See 1 more Smart Citation
“…Choline plays an important physiological role in the development and function of the cardiovascular system. Choline deficiency is associated with significant cardiovascular incidence rate and even death rate [40,41]. According to Athina a. strilakou et al, choline deficiency has an adverse effect on cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cells in the media and adventitia can migrate; and in the end, the vessels can be restored. MMP are key enzymes in the degradation of the ECM (12) and the remodeling of the vascular wall. They are zinc dependent proteolytic enzymes that have a specific role in degrading the ECM (13,14).…”
Section: Discussionmentioning
confidence: 99%